Design and performance evaluation of a compact radiation absorber for 5G applications - Khan, Imran; Alshehri, Asma; Wang, Pi-Chung; Hameed, Ibrahim A. (Frontiers in Materials, 2024)
The emergence of electromagnetic wave pollution as a new form of pollution in human society is attributed to the advancements in communication technology and the electronic information business. In addition to harming priceless electronic equipment, these electromagnetic radiation and interference issues brought on by electrical and electronic devices have a major negative influence on human productivity and well-being. The secret to getting rid of electromagnetic radiation interference (EMI) and improving performance is electromagnetic shielding technology. Metamaterial absorber is a type of metamaterial that absorb EMI radiation. The benefits of metamaterial absorbers include their lightweight, simple construction, and excellent absorptivity. This paper proposes a novel metamaterial absorber for EMI radiation absorption. It consists of dielectric layers, metamaterial shielding layer and transmission line. The reflection of radiation is reduced by miniaturization of metamaterials. Simulation results show that the proposed design has better performance as compared to existing methods. The operating frequency range is from 23.1 to 28.3 GHz. The values of S 21 with and without shielding are -5 dB and -0.05 dB, and the shielding effectiveness is 10.10 dB and a maximum of 12.63 dB.